Hubungan Dukungan Keluarga dengan Harga Diri Pasien TB Paru di Wilayah Kerja PKM Buntu Limbong Kecamatan Gandangbatu Sillana Kabupaten Tana Toraja Tahun 2020 - Yahya Handayani; Yusan Pabebang (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Family support is the attitude, action, and acceptance of the family towards sick sufferers. Through family support and a positive response from the family, it is expected that pulmonary TB patients have positive self-esteem or have high self-esteem. The purpose of this study was to determine the relationship between family support and self-esteem of pulmonary TB patients in the working area of ?? PKM Buntu Limbong, Gandangbatu Sillanan District, Tana Toraja Regency in 2020. The method used in this study was descriptive-analytic with a cross-sectional study approach. The number of subjects in this study was 34 people. Samples were taken using the total sampling technique. The measuring instrument used is a questionnaire. The data processing uses the Windows SPSS version 21 program and the data is tested with Chi-Square. The results of this study indicate that the majority of respondents with good family support are 25 people (73.5%) and the majority of respondents with positive self-esteem are 26 people (76.5%). Based on the results of the Pearson Chi-Square statistical test, the value of p = 0.017, the value of = 0.05, so p <. From the results of the study, it can be concluded that there is a relationship between family support and self-esteem of pulmonary TB patients in the working area of ?? PKM Buntu Limbong, Gandangbatu Sillanan District, Tana Toraja Regency in 2020.